2019
DOI: 10.1111/jssr.12624
|View full text |Cite
|
Sign up to set email alerts
|

Religion in Domestic Violence Prevention PSAs: The Role of Religiosity in Motivating Christian Bystanders to Intervene

Abstract: Domestic violence is an ongoing health issue around the world, propelling individuals and organizations to seek out new and innovative ways to mitigate its widespread reach. Focusing on the potential of religion to positively impact messaging, the current study examines how Christian symbolism might be used to encourage intervention behavior using public service announcements (PSAs). Using a between-subjects design of Christian Americans as the respondent pool, a religious symbol versus a control ad was utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Scholars have conceptualized and measured religiosity and spirituality with insufficient attention to their differences, but previous findings show that the two belief systems are distinct (Rinallo et al, 2012). Scholars have confirmed the effectiveness of religiosity and religious cues in domestic violence prevention messages on reporting intention (e.g., La Ferle & Muralidharan, 2019;Muralidharan et al, 2018b); however, the efficacy of spirituality and spiritual cues needs more attention in advertising research, highlighting the main purpose and contribution of the current study. In other words, can religious and spiritual cues tap into bystanders' religious/ spiritual belief system and motivate them to assist victims of domestic abuse by calling the advertised helpline number.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Scholars have conceptualized and measured religiosity and spirituality with insufficient attention to their differences, but previous findings show that the two belief systems are distinct (Rinallo et al, 2012). Scholars have confirmed the effectiveness of religiosity and religious cues in domestic violence prevention messages on reporting intention (e.g., La Ferle & Muralidharan, 2019;Muralidharan et al, 2018b); however, the efficacy of spirituality and spiritual cues needs more attention in advertising research, highlighting the main purpose and contribution of the current study. In other words, can religious and spiritual cues tap into bystanders' religious/ spiritual belief system and motivate them to assist victims of domestic abuse by calling the advertised helpline number.…”
mentioning
confidence: 76%
“…Findings from a similar study using the theory of reasoned action as a framework show that Hindu religious symbols primed religiosity, influencing attitude toward the ad and social norms about helping and strengthening intention to call the advertised helpline (Muralidharan et al, 2018b). Using a U.S. Christian sample, La Ferle and Muralidharan (2019) found that high religiosity had a stronger positive impact than a religious cue (i.e., Christian cross) on reporting intention. Participants also rated the importance of religious affiliation to their personal identity higher than church attendance and prayer.…”
Section: Study‐2mentioning
confidence: 99%
See 2 more Smart Citations
“…It also elevates social wellbeing by encouraging prosociality and encompassing ethical, cooperative, and generous behavior (Norenzayan & Shariff, 2008; Norenzayan, 2013; Pichon et al, 2007; for a review, see Shariff et al, 2016). For example, religiosity is a significant factor that motivates other people to intervene in domestic violence cases (La Ferle & Muralidharan, 2019). Aligning with this line of research, studies also show that religiosity impacts social wellbeing because religious people are more likely to offer help to others in need, and thus directs valuable social resources to where they are needed the most (Hunsberger & Platonow, 1986; Will & Cochran, 1995).…”
Section: Introductionmentioning
confidence: 99%